Analysis of Financial Literacy and Cashless Society on Financial Satisfaction through Financial Behavior in Gen Z - Vivin Vania; Wahyudi Wahyudi; Dedeh Kurniasih (Yayasan Riset dan Pengembangan Intelektual, 2023)
Generation Z (Gen Z), who grew up in the digital age, faces unique financial challenges. Despite having widespread access to financial technology, their financial literacy is not necessarily in line with technological skills. The development of a cashless society affects the way Gen Z interacts with money, which while it can make transactions easier, also requires a better understanding to control spending. This study aims to understand the complex relationship between Gen Z's financial literacy, cashless society, financial behavior, and financial satisfaction. This study uses a quantitative method with a PLS-SEM approach and data collection using a questionnaire. The results of this study indicate that of the seven hypotheses, one hypothesis is not significant, while the other six are significant. Where financial literacy has no positive and significant effect on financial satisfaction, a cashless society has a positive and significant effect on financial satisfaction, financial literacy has a positive and significant effect on financial behavior, cashless society has a positive and significant effect on financial behavior, financial behavior has a positive and significant effect on financial satisfaction. Where in the mediation test financial behavior becomes a full mediator in the relationship between financial literacy and financial satisfaction but becomes a partial mediator in the influence of cashless society on financial satisfaction.